@Home eTherapy Service for People with Common Mental Health Problems: an Evaluation. Issue 1 (16th May 2017) - Gellatly, Judith; Chisnall, Leanne; Seccombe, Nic; Ragan, Kathryn; Lidbetter, Nicola; Cavanagh, Kate
Abstract : Background: Ensuring rapid access to psychological interventions is a priority of mental health services. The involvement of peer workers to support the delivery of more accessible treatment options such as computerized cognitive behaviour therapy (CCBT) is recognized.Aims: To evaluate the implementation of a third sector remote CCBT @Home eTherapy service for people experiencing common mental health problems supported by individuals with lived experience.Method: Supported CCBT packages with telephone support were delivered over a 30-month period. Self-complete measures identifying levels of depression, anxiety and functioning were administered at each treatment appointment.Results: Over 2000 people were referred to the @Home eTherapy service; two-thirds attended an initial assessment and 53.4% of referrals assigned to CCBT completed treatment. Statistically significant improvements in anxiety, depression and functioning were found, with 61.6% of treated clients meeting recovery criteria.Conclusions: The service meets Improving Access to Psychological Therapies (IAPT) key performance targets, and is comparable to other IAPT services using CCBT. Evidence for the successful implementation of such a service by a third sector organization is provided.